Interventions in Early Diagnosis and Treatment of Acute Respiratory Tract Infections in Children Under 5 Years of Age - Amir, Muhammad; Akhater, Naheed; Sodhar, Jawad Mumtaz; Shuja, Arslan; Maqsood, Majida (Pakistan Journal of Medical & Health Sciences, 2022)
The aims and objectives of this study were early diagnosis and treatment of acute respiratory tract infections in children under 5 years of age by understang the attitued of their mothers. The findings of current study were highly significant (<0.005) and standard mean deviation levels regarding percentage of bronchitis, tonsillitis, otitis media, bronchiolitis, pneumonia in children’s of Group A boys, 23.7±3.14, 30.12±13.14, 20.22±23.10, 15.21±11.10, 10.75±10.12 and girls were 24.7±4.14, 31.10±10.11, 20.20±13.10, 14.11±10.5, 10.75±10.12 showed a significant changes as compared to the Group B boys 13.2±3.4, 10.1±10.1, 10.2±3.10, 5.20±1.10, 5.7±1.12 and girls 12.2±3.4, 11.1±10.1, 11.2±3.10, 5.10±1.10, 6.7±1.12 respectively.